Magnitude of Hepatitis B virus and associated factors among chronic liver disease patients admitted to the medical ward at Sheikh Hassen Yabare Comprehensive Specialized Hospital, Jigjiga, Ethiopia: a retrospective study - Ramadan Budul Yusuf; Getnet Addisu; Ahmed Mohammed Ibrahim; Terefe Gebre; Seid Muhumed Abdilaahi; Bilan Ali Ahmed; Abdulahi Hussen Abdinur; Girma Tadesse Wedajo; Mohamed Omar Osman (PLoS ONE, 2025)
Background Viral hepatitis is still a major public health problem around the globe, and acquiring adequate and recent epidemiological data on Hepatitis B is important in the prevention and control of the disease. Data on Hepatitis B virus (HBV) among patients with chronic liver disease are scarce in the study area, as well as in Ethiopia at large. Objective To assess the magnitude of Hepatitis B virus (HBV) and its associated factors among chronic liver disease patients admitted to the medical ward at Sheikh Hassen Yabare Comprehensive Specialized Hospital, Jigjiga, Ethiopia. Method An institution-based retrospective cross-sectional study was conducted in the Sheikh Hassen Yabare Comprehensive Specialized Hospital. A total of 249 study participants were selected by simple random sampling using a computer-generated method. A rapid test of HbsAg using a kit from Henso Medical (HANGZHOU) Co. Ltd. was used. The data were collected using Kobo toolbox and analyzed using SPSS version 29.0. Binary logistic regression was employed to identify statistically significant factors for HBV. Model fitness was checked by the Hosmer-Lemeshow goodness-of-fit test, and multicollinearity across variables was checked using the variance inflation factor. Statistical significance was considered at P < 0.05, and an adjusted odds ratio with a 95% confidence interval was used to measure the strength of the association. Result The magnitude of HBV among clinically diagnosed chronic liver disease patients was 81/249 (32.53%) (95% CI = 26.9–39.0). Having a history of hospital admission (AOR = 3.60, 95% CI = 1.84–7.04), blood transfusion history (AOR = 2.22, 95% CI = 1.13–4.37), being male (AOR = 2.65, 95% CI = 1.18–5.96) and being exposed to a jaundiced individuals (AOR = 4.52, 95% CI = 2.34–8.72) were also significantly associated with HBV. Conclusion The magnitude of HBV among clinically diagnosed chronic liver disease patients was high. Being male, having a history of hospital admission, blood transfusion, and contact history with jaundice patients were significantly associated with HBV. The hospital should strictly follow blood transfusion safety protocols and implement proper infection control measures to minimize HBV transmission. Additionally, healthcare providers should screen patients with a history of hospital admission, contact with jaundice patients to facilitate early diagnosis and treatment.